Amino acid substitutions in the human immunodeficiency virus type 1 gp120 V3 loop that change viral tropism also alter physical and functional properties of the virion envelope. - Willey, R L (1994)
The third variable (V3) region within the gp120 envelope glycoprotein of the human immunodeficiency virus type 1 (HIV-1) has been reported to be an important determinant of viral tropism. In this study a series of isogenic recombinant HIV-1 viruses, containing V3 regions from fresh isolates, were examined to ascertain if a relationship exists between viral tropism and specific properties of the virion-associated envelope. All of the viruses were able to infect CD4+ primary lymphocytes, although with different infection kinetics. Several recombinants, however, were unable to infect a continuous CD4+ T-cell line permissive for the parental virus and exhibited a marked decrease in the kinetics of virion-associated gp120 binding to a soluble form of CD4. A known macrophage-tropic HIV-1 isolate, also unable to infect the T-cell line, bound CD4 with similarly slow reaction kinetics. Although the inability to infect T-cell lines is a commonly observed property of macrophage-tropic isolates of HIV-1, the loss of T-cell line tropism by the V3 recombinants was not accompanied by a substantial infectivity for monocyte-derived macrophages, as monitored by reverse transcriptase production. Additional analyses of the recombinant virion gp120s indicated that most of the V3 substitutions increased the inherent stability of the virion gp120-gp41 envelope complex. These results indicate that V3-induced alterations in viral tropism are associated with changes in physical and functional properties of the virion envelope.